DIRECT RECONSTRUCTION OF PERMANENT DENTITION OF A PATIENT WITH AMELOGENESIS IMPERFECTA - T Kovalský; B Vágnerová; I Voborná; R Mounajjed (Czech Dental Chamber, 2020)
Introduction and aim: Amelogenesis imperfecta associates a clinically and genetically heterogeneous group of developmental defects affecting the appearance and structure of enamel, which more or less severely affect all dental functions. Manifestations of amelogenesis imperfecta are considered by patients to be a compromise of aesthetics and increased tooth sensitivity. The consequences of the disease have a detrimental effect on adolescents who integrate into groups and seek their place in society. However, the traditional treatment approach can be very expensive and may require a certain degree of psychological resilience of the patient due to the pain and time consuming treatment. These treatment requirements, together with the insufficient thickness of the secondary dentin layer, thus often force the physician to delay treatment, which may adversely affect the patient's psychosocial development. Self-observation: A fifteen-year-old patient was sent to the prosthetic department for complete reconstruction of permanent teeth with a diagnosis of hypoplastic amelogenesis imperfecta. Due to the nature of the disease, immediate direct reconstruction was performed. Conclusion: An unprepared approach is possible even in adolescence. Hard dental tissues are preserved, the vitality of the dental pulp is not endangered and the patient's psychological burden is reduced. Direct reconstruction can be approached provided the patient cooperates. This approach must be combined with consistent treatment of the tooth surface to reduce adhesion and plaque retention. The advantage is also that any partial failure of the reconstruction is relatively easy to repair in the case of direct reconstruction.